Diagnosis of amblyaudia in children referred for auditory processing assessment. (2nd June 2016) - Moncrieff, Deborah; Keith, William; Abramson, Maria; Swann, Alicia
Abstract: Children ( n  = 141) referred to 5 clinical sites for auditory processing disorder assessment were tested with two dichotic listening tests, one with word pairs and the other with pairs of digits, as part of a comprehensive diagnostic battery. Scores from the Randomized Dichotic Digits Test and the Dichotic Words Test were compared to age-appropriate norms and used to place children into one of four diagnostic categories (normal, dichotic dysaudia, amblyaudia, or amblyaudia plus) or to identify them as undiagnosed. Results from the two dichotic tests led to diagnosis of 56% of the children tested, leaving 44% undiagnosed. When results from a third dichotic listening test were used as a tie-breaker among originally undiagnosed children, a total of 79% of the children's scores were placed into diagnostic categories (13% normal, 19% dichotic dysaudia, 35% amblyaudia, 12% amblyaudia plus). Amblyaudia, a binaural integration deficit evident only from dichotic listening test results, was most prevalent (35% + 12% = 47%) in this population of children suspected of auditory processing weaknesses. Since amblyaudia responds to treatment with Auditory Rehabilitation for Interaural Asymmetry (ARIA), clinicians are guided through the protocol for identifying diagnostic categories so that they can make appropriate referrals for rehabilitation.